KEBIJAKAN PENDIDIKAN KETERAMPILAN DI PONDOK PESANTREN - Royani (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2014)
Boarding school is a potential and thus has a strategic position, the empowerment efforts boarding school as educational institutions and social organizations to develop human resources professionals is a must, depelovment human reseuses can be done by implementing life skills education. Since the beginning of its existence until now and in the days to come, Boarding Schools in addition to functioning as a religious institution, also serves as a center for community development and human resource development center that is Qualified. When examined in more depth, boarding school is not an institution that will foster the emergence of religious fanaticism, but is an institution that has the potential to be typical, which if developed optimally be able to contribute to the formation of character and personality of the nation.